2006
DOI: 10.1016/j.febslet.2006.10.037
|View full text |Cite
|
Sign up to set email alerts
|

A model of tenascin‐X integration within the collagenous network

Abstract: Tenascin-X is an extracellular matrix protein whose absence leads to an Ehlers-Danlos syndrome in humans, characterized mainly by disorganisation of collagen and elastic fibril networks. After producing recombinant full-length tenascin-X in mammalian cells, we find that this protein assembled into disulfide-linked oligomers. Trimers were the predominant form observed using rotary shadowing. By solid phase interaction studies, we demonstrate that tenascin-X interacts with types I, III and V fibrillar collagen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 22 publications
(31 reference statements)
0
66
0
2
Order By: Relevance
“…It has been shown in vitro that decorin and tenascin-X interact with the fibrillar collagens (particularly type I) (Svensson et al, 1995;Lethias et al, 2006), and that type XIV collagen interacts with decorin (Font et al, 1996;Ehnis et al, 1997;Elefteriou et al, 2001). Tenascin-X and collagen XIV could modulate the flexibility of the ECM and, as a result, its mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in vitro that decorin and tenascin-X interact with the fibrillar collagens (particularly type I) (Svensson et al, 1995;Lethias et al, 2006), and that type XIV collagen interacts with decorin (Font et al, 1996;Ehnis et al, 1997;Elefteriou et al, 2001). Tenascin-X and collagen XIV could modulate the flexibility of the ECM and, as a result, its mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, we can mention collagen XIV, a minor collagen, decorin, a proteoglycan (PG) and tenascin-X, a noncollagenic glycoprotein (Velleman, 2002). They interact with structural collagens and each other (Font et al, 1993;Weber et al, 1996;Elefteriou et al, 2001;Lethias et al, 2006) and are co-localized in perimysium (Listrat). These interactions might have important biological implications on building of extracellular networks, alter flexibility of the ECM and, as a result, its mechanical properties (Nishiyama et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…They interact with other ECM molecules such as decorin (Font et al, 1998) or tenascin-X (Lethias et al, 2006), they promote collagen gel contraction in vitro (Nishiyama et al, 1994), but their respective roles are still unclear. Collagen XII could form flexible bridges between collagen fibrils by interacting with them both directly and indirectly by its binding partners.…”
Section: Collagen XII and Xivmentioning
confidence: 99%
“…Recombinant full length bovine TNX was produced in mammalian HEK293 cells as previously described [7,10]. TNX was further purified from the culture medium by two chromatographic steps: firstly on heparin-Sepharose (GE Healthcare), and secondly on Q-Sepharose (GE Healthcare) [7].…”
Section: Production and Purification Of Recombinant Tnxmentioning
confidence: 99%
“…This association might be explained by the interaction of TNX with several molecular components of these fibrils i.e. decorin, fibrillar and FACIT collagens [6,7,8]. More recently, it was shown that TNX has elastic properties, due to the extension/refolding of its constitutive FNIII modules [9].…”
Section: Introductionmentioning
confidence: 99%